2023
DOI: 10.1088/2752-5309/accd10
|View full text |Cite
|
Sign up to set email alerts
|

Association between traffic-related air pollution exposure and fertility-assisted births

Abstract: Previous studies have suggested that traffic-related air pollution is associated with adverse fertility outcomes, such as reduced fecundability and subfertility. The purpose of this research is to investigate if PM2.5 exposure prior to conception or traffic-related exposures (traffic density and distance to nearest major roadway) at birth address is associated with fertility-assisted births. We obtained all live and still births from the Massachusetts state birth registry with an estimated conception date betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…On the other hand, a lack of meaningful association between traffic-related air pollution exposure and fertility-assisted births was reported in a retrospective study conducted by Thampy and Vieira, based on data attained from the Massachusetts state birth registry [122]. However, they found that fertility-assisted births were associated negatively with traffic density and positively with distance from major roadways [122]. Furthermore, a similar study utilizing national data in the USA did not show any correlation between reproductive outcomes and average daily concentrations of PM 2.5 and O 3 [123].…”
Section: Effects Of Air Pollution On Reproductive Outcomesmentioning
confidence: 99%
“…On the other hand, a lack of meaningful association between traffic-related air pollution exposure and fertility-assisted births was reported in a retrospective study conducted by Thampy and Vieira, based on data attained from the Massachusetts state birth registry [122]. However, they found that fertility-assisted births were associated negatively with traffic density and positively with distance from major roadways [122]. Furthermore, a similar study utilizing national data in the USA did not show any correlation between reproductive outcomes and average daily concentrations of PM 2.5 and O 3 [123].…”
Section: Effects Of Air Pollution On Reproductive Outcomesmentioning
confidence: 99%
“…They found no significant solid adverse association between trafficconnected air pollution exposure and fertility-assisted births. Further studies in more highly exposed study areas are needed to draw inferences [42].…”
Section: Road Traffic Linked Pollutants and Female Reproduction Or Pr...mentioning
confidence: 99%